Euthanasia: The conceptualization of the problem and important distinctions - Đerić Milijana (Filozofija i Društvo, 2013)
The aim of this work is twofold. On the one hand, the intention is to provide analysis of the issue of euthanasia. On the other hand, this approach necessarily leads to a discussion toward the provision of an adequate definition of euthanasia. Therefore the article, first of all, refers to the multilayered aspect of the term euthanasia. To avoid ambiguity and other uncertainties while providing the definition of euthanasia, the authors carefully perform a conceptual analysis. This leads to the establishment of a clear distinction between actions which, due to their motives or their method of execution, cast a shadow on the meaning of this medical procedure. [Projekat Ministarstva nauke Republike Srbije, br. 179041: Dinamički sistemi u prirodi i društvu: filozofski i empirijski aspekti]